Synthesis of Acid Mucopolysaccharides by Glial Tumor Cells in Tissue Culture - Dorfman, Albert (1970)
A clonal strain of rat glial tumor cells was shown to produce the acid mucopolysaccharides, hyaluronic acid, chondroitin 4-SO(4), and heparan sulfate in tissue culture. The mucopolysaccharides were isolated both from the growth medium and the cells.